Banking development and economy in Greece: Evidence from regional data - Christos Floros (Journal of Risk and Financial Management, 2020)
This article examines the development of Greek systemic banks for the period 2003-2018, using data such as the ATM network and branches at a regional level. We test the impact of the ATM network and branches on the deposits of Greek commercial banks as well as the impact of local GDP on the regional banking efficiency. The analysis is carried out in two steps, (1) we use the Data Envelopment Analysis (DEA) for efficiency analysis, and (2) we use panel regression models for regression analysis. The results show that branches that operate at small regions are less efficient than those of the larger regions. Furthermore, both the ATMs and the number of branches have a positive relationship with deposits. This means that banks must continue to operate branches and ATMs in Greece. Finally, we show that local GDP helps significantly in increasing regional banking efficiency. The above findings are important given the need to support the local economy with modern banking services in Greece.
Keywords: 330; ATM network; branch network; deposits; efficiency; Greek banks; Greek regions; local GDP; panel data